Integrating Miro into The Picture Word Inductive Model (PWIM) to Enhance Collaborative Writing in EFL Instruction: - Dewi, Adinda Kharisma; Sumarta; Dewi, Indah Purnama (PROJECT (Professional Journal of English Education), 2026)
This study explores the integration of Miro, a digital visual collaboration platform, into the Picture Word Inductive Model (PWIM) to enhance collaborative writing among eighth-grade students in an English as a Foreign Language (EFL) context. Employing a qualitative case study design, data were collected through classroom observations, student interviews, and document analysis of student writing. The integration of Miro addressed key challenges in vocabulary development and idea organization, while also fostering student engagement, peer interaction, and structured language production. Students reported increased motivation, reduced writing anxiety, and greater confidence in expressing their ideas. Miro’s visual tools supported brainstorming, sequencing, and revision activities, enabling learners to develop not only their linguistic abilities but also critical thinking and digital communication skills. The findings highlight the pedagogical value of combining inductive teaching models with interactive digital platforms to support student-centered, collaborative learning in EFL instruction.